Crime in more-developed states in Malaysia: its determinants and estimation of economic costs - Suryati Ishak (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2012)
Crime is a major public concern besides other issues such as economics and politics among Malaysians. Lately, the crime problem in Malaysia has received considerable attention and extensive coverage in newspapers and the electronic media. This research examines the relationship between crime and its determinants in Malaysia by using a panel data analysis. A comparison between the states, namely Kuala Lumpur, Selangor, Johor and Pulau Pinang was made by using the crime data for the period 1990 through 2005. A Pooled OLS regression using eight variables, ie; real GDP per capita, unemployment rate, education rate, total population, population density, divorce rate, number of police officers and the number of cases solved were used. Only three variables were found significant to explain for total crime rate; they were real GDP per capita, unemployment rate, and number of police officers. In addition to that, this paper also estimated the monetary costs of crime. For the purpose of this study, only immediate impact of monetary value was calculated, for example indirect costs are not included in the costs estimation. The aggregate burden of the six types of crime, ie; assault, murder, burglary, vehicle theft, house breaking, and other theft, estimated was around RM3, 028 million. Analysis by category of cost found that the highest cost borne by the population in Malaysia was related to vehicle thefts (RM1, 636 million). In the meantime, housebreaking, assault and other theft exhibited lower costs per incidents. Moreover, this research also examines the perceptions on crime in Malaysia. The results show that, female respondents were significantly more fearful than males; female respondents perceived walking during the day was fairly safe while male respondents perceived it as safe. Furthermore, female respondents perceived walking at night as unsafe and male respondent perceived as fairly safe.